2007
DOI: 10.1007/s11606-007-0106-7
|View full text |Cite
|
Sign up to set email alerts
|

Living Alone, Patient Sex and Mortality After Acute Myocardial Infarction

Abstract: BACKGROUND: Psychosocial factors, including social support, affect outcomes of cardiovascular disease, but can be difficult to measure. Whether these factors have different effects on mortality post-acute myocardial infarction (AMI) in men and women is not clear. OBJECTIVE:To examine the association between living alone, a proxy for social support, and mortality postdischarge AMI and to explore whether this association is modified by patient sex.DESIGN: Historical cohort study. PARTICIPANTS/SETTING:All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 25 publications
8
76
2
1
Order By: Relevance
“…Moreover, living alone could play a part as a predictor of increased risk for long-term mortality in patients suffering from MI. This is especially significant for male patients, but even women living alone have a higher risk compared to women living in a relationship [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, living alone could play a part as a predictor of increased risk for long-term mortality in patients suffering from MI. This is especially significant for male patients, but even women living alone have a higher risk compared to women living in a relationship [8].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond marital status, we do not have sufficient detail to further describe patients' social support where added care-provider networks may exist. 30,31,35 Considering followup, 15 months may not be sufficient time to observe significant effects of marital status on CV risk following MI, with other reports noting significant effects at 3 years among patients with CVD and 10 years among patients with hyperlipidemia, respectively. 9,10 Moreover, we did not account for recurrent CV events in our analysis, and this may underestimate the total burden of MI and stroke.…”
Section: Study Limitationsmentioning
confidence: 97%
“…In married vs unmarried men and women, past studies highlighted differences in outcomes following an MI. 21,24,25,[29][30][31] It was observed that women receive less informal caregiver support than do men, with worse outcomes, 1 to 12 months following an MI. 25 However, in contrast with many of the prior studies that controlled simply for certain socioeconomic determinants of health, such as income and education, we additionally adjusted for differences in baseline comorbidities that may have attenuated any association with marital status.…”
Section: Following Logistic Regression and Cox Proportional Hazarmentioning
confidence: 99%
“…In fact, social aspects are given scant consideration in the trials as possible predictive factors of mortality [32,33] and rehospitalization [34,35].…”
Section: Introductionmentioning
confidence: 99%